Periodontio-integrated implants: A revolutionary concept - Minkle Gulati; Vishal Anand; Vivek Govila; Nikil Jain; Pavitra Rastogi; Rohit Bahuguna; Bhargavi Anand (Wolters Kluwer Medknow Publications, 2014)
Though the fields of regenerative dentistry and tissue engineering have undergone significant advancements, yet its application to the field of implant-dentistry is lacking; in the sense that presently the implants are being placed with the aim of attaining osseointegration without giving consideration to the regeneration of periodontium around the implant. The following article reveals the clinical benefits of such periodontio-integrated implants and reviews the relevant scientific proofs. A comprehensive research to provide scientific evidence supporting the feasibility of periodontio-integrated implants was carried out using various online resources such as PubMed, Wiley-Blackwell, Elsevier etc., to retrieve studies published between 1980 and 2012 using the following key words: "implant," "tissue engineering," "periodontium," "osseo-integration," "osseoperception," "regeneration" (and their synonyms) and it was found that in the past three decades, several successful experiments have been conducted to devise "implant supported by the periodontium"that can maintain form, function and potential proprioceptive responses similar to a natural tooth. Based on these staunch evidences, the possibility of the future clinical use of such implant can be strongly stated which would revolutionize the implant dentistry and will be favored by the patients as well. However, further studies are required to validate the same.